Digital Signal Processing Using MATLAB : A Problem Solving Companion - Vinay K. Ingle Proakis, John G. (India : Cengage Learning, 2017)
Engineering
Keywords: Digital Signal -- Signal Processing -- MATLAB; MATLAB Functions -- FIR Filter -- Digital Filters -- LTI Systems